Contending Geo-Logics: Energy Security, Resource Ontologies, and the Politics of Expert Knowledge in Estonia. Issue 4 (1st October 2016) - Kama, Kärg
ABSTRACT: Engaging with nascent scholarly efforts to foreground the 'geo' of geopolitics, this article examines how certain low-quality geological substances are constituted as strategic, 'unconventional' fossil fuel resources, the exploitation of which is deemed indispensable for energy security reasons. Based on a detailed study of oil shale exploitation in Estonia, the paper specifically analyses the politics of knowledge that enable such carbon-intensive and energy-inefficient industries to perpetuate at the national level and, moreover, subvert the neoliberal imperatives of energy sector deregulation and decarbonisation arising from EU policies. This analysis leads to two key arguments. At one level, the Estonian case evidences and contextualises the growing recognition that 'energy security' represents a multifaceted and dynamic construct as it highlights, in particular, the contingency of expert knowledge in its conceptualisation and performance. What counts as energy security is in this case articulated via shifting and contested modes of knowledge-making, whereby state- and market-led modes of energy governance are continuously renegotiated. At another level, however, the politics of knowledge is explained here as exercised through contending ontologies of the fossil fuel resource that pivots security claims, or 'geo-logics', which has multiplying effects on resource materiality.